Legality of Execution of Collateral Based on Electronic Mortgage Certificate in Bank Credit Agreement - Sriono Sriono; Kusno Kusno; Risdalina Risdalina; Wahyu Simon Tampubolon; Indra Kumalasari M. (Budapest International Research and Critics University, 2021)
This study aims to analyze the legality of the electronic certificate of mortgage in the context of executing the guarantee if the debtor defaults or defaults if there is a data error in the bank credit agreement. The method used in this research is the literature method with reference to the normative juridical method, namely using data sourced from secondary legal materials, namely from the prevailing laws and regulations in Indonesia. The regulations used as material are the Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency of the Republic of Indonesia Number 3 of 2019 concerning Electronically Integrated Mortgage Services. The research results show that the certificate generated from the electronic mortgage registration system has executorial power because the mortgage certificate contains the sentence for Justice Based on the One Godhead. The sentence shows that the mortgage certificate can be used as a tool for executing collateral if the debtor defaults or defaults to pay without a court order. Sentences for Justice based on the One Godhead are equated as a judge's decision in a court. If there is a data error in the certificate and no changes are made, the execution cannot be carried out and the certificate can be canceled and the agreement in guarantee can also be canceled.